2016
DOI: 10.1227/neu.0000000000001409
|View full text |Cite
|
Sign up to set email alerts
|

Worse Outcomes After Repeat vs Initial Stereotactic Radiosurgery for Cerebral Arteriovenous Malformations

Abstract: AVM, arteriovenous malformationRIC, radiation-induced changeRBAS, radiosurgery-based arteriovenous malformation scoreSRS, stereotactic radiosurgeryVRAS, virginia radiosurgery AVM scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…However, Feutren et al 54 reported a much higher rate of radiologic brain edema (66%) in his series of 48 patients treated with CyberKnife (Accuray, Sunnyvale, California, United States) for AVMs. Ding et al 51 reported that the rates of radiologic, symptomatic, and permanent RICs (35%, 10%, and 4%, respectively) were not significantly different in the two cohorts of patients with repeat SRS versus those with initial SRS. Matsuo et al 52 reported post-LINAC-SRS actuarial symptomatic radiation injury rates of 12.3%, 16.8%, and 19.1%, at 5, 10, and 15 years, respectively, and they recommended long-term observation after SRS for AVMs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Feutren et al 54 reported a much higher rate of radiologic brain edema (66%) in his series of 48 patients treated with CyberKnife (Accuray, Sunnyvale, California, United States) for AVMs. Ding et al 51 reported that the rates of radiologic, symptomatic, and permanent RICs (35%, 10%, and 4%, respectively) were not significantly different in the two cohorts of patients with repeat SRS versus those with initial SRS. Matsuo et al 52 reported post-LINAC-SRS actuarial symptomatic radiation injury rates of 12.3%, 16.8%, and 19.1%, at 5, 10, and 15 years, respectively, and they recommended long-term observation after SRS for AVMs.…”
Section: Discussionmentioning
confidence: 99%
“…These changes, usually observed from 6 to 18 months after SRS, are frequently transient and reversible (i.e., resolving over weeks or a few months). 4,11,22,26,27,[51][52][53][54] Ilyas et al, 53 based on pooled data from 51 studies, reported that $ 1 in 3 patients with AVMs treated with SRS develops radiologically evident RIC, and of those, 1 in 4 patients develops neurologic symptoms. The present study showed 20.9%, 33.9%, and 12.9% rates of transient, persistent, and symptomatic RICs, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, prior nidal embolization has been shown to be a negative prognostic factor for post-SRS AVM obliteration, and repeat SRS may yield worse outcomes than initial SRS. 10,21 Due to the risk of hemorrhage and its associated morbidity and mortality, complete nidal obliteration remains the primary goal of any AVM treatment. SRS is an effective treatment for pediatric AVMs, especially for those not amenable to surgery, with reported obliteration rates ranging from 60% to 80% at 4-5 years after SRS.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated risk of both initial and repeat hemorrhage for these deep-seated CCMs compared to cortical CCMs favors intervention, whereas the relatively high rate of neurological morbidity associated with surgical resection of these lesions supports a more conservative approach 41)42). Although radiosurgery is a conceptually attractive alternative to surgical resection of eloquent CCMs, the radiosurgery-induced complication rate is significantly higher for CCMs than for AVMs, and CCMs cannot be radiologically monitored for obliteration after radiosurgery 3)5)6)8)9)10)12)13)14)15)16)17)18)19)20)21)22)23)25)26)27)28)29)30)31)32)33)34)35)36)37)43)44)49)50)52)53)56)59)63)64)65)66)67)68). Instead, the proposed effect of radiosurgery on CCMs is a decreased risk of symptomatic hemorrhages, which is controversial due to temporal clustering of CCM hemorrhages 4).…”
Section: Discussionmentioning
confidence: 99%